Physical determinants, intercorrelations, and relevance of movement speed components in elite junior tennis players - Vuong, J. L.; Fett, J.; Ulbricht, A.; Ferrauti, A. (European Journal of Sport Science, 2022)
Movement speed is considered essential for success in elite tennis. The aim of the present study was to develop a model of movement speed components and quantify their age- and gender-related relevance for tennis performance. Physical testing data obtained from 1,434 nationally ranked junior squad tennis players were divided according to the age at peak height velocity (YPHV) into two age groups (pre-PHV: n=103 girls, 11.7 ± 0.6 yrs.; n=466 boys, 12.7 ± 1.0 yrs.; post-PHV: n=524 girls, 14.2 ± 1.4 yrs.; n=344 boys, 15.3 ± 1.2 yrs.). After assessing anthropometrics and maturity status, all players passed a series of standardized physical tests on an indoor hard court. All data were z-standardized, filtered and sorted by gender, maturity level, and ranking position. The structuring of the speed-related performance parameters resulted in four factors (`Elementary Speed`, `Jumping Power`, `Linear Speed`, and `COD Speed`), which were then confirmed by factor analysis. The correlation of these factors to the national ranking position was mostly significant but rather low, with `Linear Speed` reaching the lowest (r=0.10-0.18) and `COD Speed` the highest correlation (r=0.22-0.34). Path analytic models revealed `COD Speed` as the most important factor, which is strongly influenced by `Jumping Power` and `Linear Speed,` with medium effect sizes, while `Elementary Speed` affects this factor only slightly. It can be concluded that the relationship between movement speed and junior players` tennis ranking is lower than expected. The development of `COD Speed` should be prioritized during testing, training, and talent identification, independent of age group and gender.